ACTR-51. PHASE 2 STUDY TO EVALUATE THE SAFETY, PHARMACOKINETICS AND CLINICAL ACTIVITY OF PI3K/MTOR INHIBITOR GDC-0084 GIVEN TO GLIOBLASTOMA (GBM) PATIENTS WITH UNMETHYLATED O6-METHYLGUANINE-METHYLTRANSFERASE PROMOTER STATUS. (5th November 2018) - Wen, Patrick; Cloughesy, Timothy; de Groot, John; Battiste, James; Garner, James; Simpson, Jeremy; Olivero, Alan; Gerstner, Elizabeth
Abstract: BACKGROUND: GDC-0084 is a potent, oral, selective small molecule inhibitor of class I phosphoinositide 3-kinase and mammalian target of rapamycin (PI3K/mTOR) efficacious in GBM models driven by activation of the PI3K pathway. GDC-0084 crosses the blood-brain barrier (BBB) and achieves a brain / plasma ratio of approximately 1.0 in three animal species. GDC-0084 was given as once daily oral dosing in a phase 1 study (Wen et al, J Clin Oncol 34, 2016(15) suppl.2012; NCT01547546) in 47 patients with recurrent high-grade gliomas. The adverse events were generally consistent with the established Class I PI3K/mTOR inhibitor class-effects. GDC-0084 was rapidly absorbed and demonstrated linear- and dose-proportional increases in exposure. The MTD was determined to be 45 mg once daily, with 7/8 patients receiving this dose having drug exposures consistent with anti-tumor activity in pre-clinical models. Fluorodeoxyglucose-positron emission tomography (FDG-PET) scans suggested that GDC-0084 crossed the BBB, with a uniform distribution throughout the brain. The current phase 2 study will investigate the efficacy and safety of GDC 0084 in patients with newly diagnosed GBM, with unmethylated O6-methylguanine-methyltransferase (MGMT) promoter status. METHODS: This protocol (NCT03522298) has a 2-part design. The phase 1b component consists of an open-label, multicenter dose-escalation study with expansion assess the safety, tolerability, RP2D, PK and clinical activity of GDC 0084 in patients with newly-diagnosed GBM with unmethylated MGMT. The dose-escalation portion of the study will use a standard "3 + 3" design to determine the MTDs for QD, QOD and 3 days on/4 days off schedules. At each of the identified MTDs 10 subjects will be recruited in an expansion cohort. The RP2D will be selected from the three dose schedules being tested. The phase 2 component will evaluate clinical activity of GDC-0084 at the RP2D vs temozolomide as adjuvant therapy following surgical resection and chemoradiation in 224 patients.